A novel approach to assessing the commercial opportunities for greenhouse gas removal technology value chains: Developing the case for a negative emissions credit in the UK. (1st December 2018) - Platt, Devon; Workman, Mark; Hall, Stephen
Abstract: In the UK the development of greenhouse gas removal (GGR) technologies at scale by 2050 is seen as an increasingly urgent imperative; necessary to ensure alignment of the UK's carbon targets with international efforts to limit the global temperature increase to 2 °C or less. As such, GGR is an increasingly critical topic for UK climate policy. So far, GGR research has focused on top-down assessment of techno-environmental potential and carbon abatement costs - an approach which aids integrated assessment modelling but does not provide the commercially relevant analysis necessary to understand potential routes to market for this sector. This research reduces this knowledge gap by employing a novel bottom-up perspective to determine the financial opportunities available to GGR business models in Biomass heavy UK energy scenarios. This delivers results relevant to national and sectorial policy and decision making, by quantifying revenue opportunities from future GGR value chains, as well as business model performance. It also informs the innovation, policy, and regulatory environment required to ensure market development and resilience of different revenue streams. The work concludes that energy market policy - specifically access to a carbon credit mechanism - has by far the greatest near term opportunity to drive the negative emissions technologies we assess. This is because the values in this market far outweigh those in related supply chains such as: enhanced oil recovery, afforestation payments, biochar markets, and industry and commercial uses of captured carbon. This data shows that negative emissions technologies in the UK, should not be led by agricultural and land use policy, but should be integrated with energy policy. To do this, the development of a carbon storage credit mechanism analogous to the existing carbon price floor is key. As a proof of concept for a novel method to generate commercially relevant insights for GGR scale up, the research clearly demonstrates that the value pool method provides critical insights to assist GGR development and could form the basis of further work. Highlights: A novel bottom up model generates commercial analysis for Greenhouse Gas Removal (GGR) innovation and deployment. GGR value chains can access value of £35.3bn to £36.9bn by 2050 in future scenarios developed. Electricity generation and carbon credit value pools are fundamental to scaling GGR. A distributed biomass-focused pathway to deployment enables greatest value capture and mitigates risk. The introduction of a negative emission credit mechanism for net CO2 removal is essential.